Effects of Berberine on the Chondrogenic Differentiation of Embryonic Limb Skeletal Progenitors - Duarte-Olivenza C; Montero JA; Lorda-Diez CI (Dove Medical Press, 2021)
Cristina Duarte-Olivenza, Juan Antonio Montero, Carlos Ignacio Lorda-Diez Departamento de Anatomía y Biología Celular and IDIVAL, Universidad de Cantabria, Santander, 39011, SpainCorrespondence: Carlos Ignacio Lorda-DiezDepartamento de Anatomía y Biología Celular and IDIVAL, Universidad de Cantabria, Santander, 39011, SpainTel +34 942201570Fax +34 942201923Email lordaci@unican.esIntroduction: Berberine (BBR) is an isoquinoline plant alkaloid with demonstrated anti-inflammatory, anti-tumor and immunosuppressive pharmacological properties that functions via multiple signaling pathways and epigenetic modulators. Numerous studies have proposed BBR as a promising therapeutic agent for joint cartilage degeneration, and other connective tissue diseases.Purpose and Methods: This work aimed to evaluate the effects of BBR on the growth and differentiation of embryonic skeletal progenitors using the limb mesoderm micromass culture assay.Results: Our findings show that at difference of its apoptotic influence on a variety of tumor tissues, cell death was not induced in skeletal progenitors by the addition of 12 or 25 μM BBR concentration to the culture medium. Morphological and transcriptional analysis revealed dual and opposite effects of BBR treatments on chondrogenesis depending on the stage of differentiation of the cultured progenitors. At early stage of culture, BBR was a potent chondrogenic inhibitor, while chondrogenesis was intensified in treatments at advanced stages of culture. The chondrogenic promoting effect was accompanied by a moderate upregulation of gene markers of prehypertrophic cartilage, including ColXa1, alkaline phosphatase Alpl, Runx2, and Indian Hedgehog Ihh. We further observed a positive transcriptional influence of BBR in the expression of DNA methyltransferase genes, Dnmt1, Dnmt3a and Dnmt3b, suggesting a potential involvement of epigenetic factors in its effects.Conclusion: Our study uncovers a new pharmacological influence of BBR in cartilage differentiation that must be taken into account in designing clinical protocols for its employment in the treatment of cartilage degenerative diseases.Keywords: chondrogenesis, osteoarthritis, cartilage differentiation, DNA methyltransferases